2020
DOI: 10.3390/ijerph17218052
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Occurrence and Distress after Heart Transplantation—A Nationwide Cross-Sectional Cohort Study

Abstract: Experiencing symptoms after heart transplantation may hamper the heart recipient’s self-management which can lead to negative effects. We know little about symptom occurrence and distress after heart transplantation, especially in relation to sociodemographic variables. The aim of the study was to explore self-reported symptom occurrence and distress after heart transplantation and their relationship with self-reported psychological well-being and sociodemographic factors. This multicenter, cross-sectional, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 26 publications
(46 reference statements)
4
23
0
Order By: Relevance
“…Fatigue is one of the frequently reported symptoms after heart transplantation, 15,16 and it is reported in the literature that fatigue should be evaluated in this patient group. 13 Similar to the literature, fatigue was determined to be one of the most frequently reported symptoms in our study. Many factors contribute to the emergence of fatigue after heart transplantation, and it is claimed that fatigue is one of the most common symptoms associated with immunosuppressive treatment in organ transplant patients.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Fatigue is one of the frequently reported symptoms after heart transplantation, 15,16 and it is reported in the literature that fatigue should be evaluated in this patient group. 13 Similar to the literature, fatigue was determined to be one of the most frequently reported symptoms in our study. Many factors contribute to the emergence of fatigue after heart transplantation, and it is claimed that fatigue is one of the most common symptoms associated with immunosuppressive treatment in organ transplant patients.…”
Section: Discussionsupporting
confidence: 79%
“…11 In another study, it was found that shortness of breath, bloating, nausea-vomiting, appetite problems, diarrhea, itchy skin, headache, pain, tremor in the hands, dizziness, feeling sad, and decreased libido were commonly experienced symptoms in the first 2 years after heart transplantation. 13 Similarly, in our study, in which the symptoms in the first 5 years of heart transplantation were evaluated, it was determined that fatigue, pain in the back, neck, and joints, restlessness/agitation, weight gain, and edema in the lower extremities were the most common symptoms, and skin spotting, insomnia, pain at the surgical site, palpitation, and appetite problems were other symptoms observed in more than half of the patients in this study. Fatigue is one of the frequently reported symptoms after heart transplantation, 15,16 and it is reported in the literature that fatigue should be evaluated in this patient group.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Each response is assessed on a five‐point scale ranging from “not at all” to “very much.” Patient scores are summed, and lower scores indicate better well‐being. Studies support the psychometric properties of the OTSWI as an instrument for measuring SD and well‐being in solid‐organ transplantation 58,59 . All eight subscales have satisfactory internal consistency measured by Cronbach's alpha >.81 57 .…”
Section: Resultsmentioning
confidence: 69%
“…Studies support the psychometric properties of the OTSWI as an instrument for measuring SD and well-being in solid-organ transplantation. 58,59 All eight subscales have satisfactory internal consistency measured by Cronbach's alpha >.81. 57 It has satisfactory internal convergent validity as well as good discriminatory validity for each item and overall.…”
Section: Organ Transplant Symptom and Well-being Instrument (Otswi)mentioning
confidence: 98%